2008
DOI: 10.1103/physrevb.77.085419
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of aMn6(S=4)single molecule magnet grafted on Au(111)

Abstract: Single molecule magnets ͑SMMs͒ form a new class of magnetic materials consisting of identical nanoscale particles that can show magnetization in the absence of a magnetic field. We have experimentally and theoretically investigated the low-spin ͑S=4͒ member of the Mn6 SMM family, properly functionalized with two 3-thiophenecarboxylate ͑3tpc͒ ligands in order to graft it on to a Au͑111͒ surface. We report the theoretical density of states calculated within the local density approximation ͑LDA͒ scheme accounting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…However, the value of this parameter is uncertain for nanoparticles and clusters which are characterized by large surface-to-volume ratio, reduced coordination, low dimensionality, and symmetry. In all previous theoretical studies of magnetic clusters [1,2], alloys [3][4][5], magnetic molecules [6,7], and adatoms on graphene [8], the value of U is usually taken from bulk materials and assumed to be unchanged. However, it has been reported that the value of Hubbard U for an isolated atom is about three to five times larger than an atom in a bulk solid [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the value of this parameter is uncertain for nanoparticles and clusters which are characterized by large surface-to-volume ratio, reduced coordination, low dimensionality, and symmetry. In all previous theoretical studies of magnetic clusters [1,2], alloys [3][4][5], magnetic molecules [6,7], and adatoms on graphene [8], the value of U is usually taken from bulk materials and assumed to be unchanged. However, it has been reported that the value of Hubbard U for an isolated atom is about three to five times larger than an atom in a bulk solid [9].…”
Section: Introductionmentioning
confidence: 99%
“…In order to build devices including magnetic molecules, stable monolayers of magnetic molecules must be formed on various substrates, and mechanisms of interactions between molecules and substrates should be understood. A great progress has been made for deposition of various SMMs, such as prototype SMM Mn 12 [3][4][5][6][7][8] , Mn 6 9 , Fe 4 10 , Cr 7 Ni 11 , and TbPc 2 12 , on metallic, semiconducting, or superconducting substrates 13 . Electronic and magnetic properties of SMMs on substrates were characterized using x-ray absorption and photoemission spectroscopy 4,6,[9][10][11] , scanning tunneling microscopy (STM) 3,7,12 , β-detected nuclear magnetic resonance 5 , and x-ray magnetic circular dichroism (XMCD) 8,10 .…”
Section: Introductionmentioning
confidence: 99%
“…A great progress has been made for deposition of various SMMs, such as prototype SMM Mn 12 [3][4][5][6][7][8] , Mn 6 9 , Fe 4 10 , Cr 7 Ni 11 , and TbPc 2 12 , on metallic, semiconducting, or superconducting substrates 13 . Electronic and magnetic properties of SMMs on substrates were characterized using x-ray absorption and photoemission spectroscopy 4,6,[9][10][11] , scanning tunneling microscopy (STM) 3,7,12 , β-detected nuclear magnetic resonance 5 , and x-ray magnetic circular dichroism (XMCD) 8,10 . On the theoretical front, the electronic structure and magnetic properties of a SMM Mn 12 monolayer adsorbed on Au were studied using densityfunctional theory (DFT) 14 .…”
Section: Introductionmentioning
confidence: 99%
“…(2) and (16). Renormalization of the easy-axis anisotropy by rotations can be presented in the form K ′ = K (1 − ǫ), where…”
mentioning
confidence: 99%
“…Later, beams of small magnetic clusters were investigated [7][8][9][10][11][12] and more recently free magnetic nanoparticles confined within solid nanocavities have been studied 6 . Experimentalists have also worked with molecular nanomagnets deposited on surfaces [13][14][15][16] or carbon nanotubes 17 , as well as with single magnetic molecules bridged between metallic electrodes [18][19][20][21][22] . In such experiments the particles retain some mechanical freedom.…”
mentioning
confidence: 99%